Injuries in female and male elite taekwondo athletes: a 10-year prospective, epidemiological study of 1466 injuries sustained during 250 000 training hours - Park, K. J.; Song, B. B. (British Journal of Sports Medicine, 2018)
Objectives: We aimed to determine the injury patterns associated with training activities in elite South Korean taekwondo athletes training for the Olympic Games.